PELATIHAN UNTUK MENINGKATKAN KEMAMPUAN DALAM MEMIMPIN DAN MOTIVASI BAGI TENAGA PROFESSIONAL DI BANJARBARU - Hidayatullah, Muhammad Syarif; Thaibah, Hayatun; Nugraha, Ahmad Helmi; Nuzula, Muhammad Firdaus (Universitas Pelita Harapan, 2022)
Factors that affect performance and productivity in teaching include: competence, work motivation, work ability, work discipline, work cooperation, leadership and social status of educators. The results of research conducted by Hidayatullah & Thaibah (2021) showed that there was a decrease in aspects of work motivation, cooperation, work discipline, and leadership in working in the world of education so that there was an increase in these aspects, training was carried out. This increase was carried out on the aspects of work motivation and cooperation. The target of this training is professionals. These professionals are principals, teachers and education staff. In connection with the above, this training is given to professionals who work at the Creative Islamic Elementary School in Banjarbaru City, South Kalimantan, Indonesia. This training was attended by 20 participants, namely educators and staff. This training process has 2 processes, indoors and outdoors. In the room, it is done by giving material about leadership and motivation. While outside the room, application activities are carried out through simulations on leadership and motivationabstract in bahasaFaktor yang mempengaruhi kinerja dan produktivitas dalam mengajar antara lain : kompetensi, motivasi kerja, kemampuan kerja, disiplin kerja, kerjasama kerja, kepemimpinan dan status sosial pendidik. Hasil penelitian yang dilakukan oleh Hidayatullah & Thaibah (2021) menunjukkan ada penurunan yaitu pada aspek motivasi kerja, kerjasama disiplin kerja, dan kepemimpinan dalam bekerja di dunia pendidikan agar ada peningkatan terhadap aspek-aspek tersebut maka dilakukanlah pelatihan. Peningkatan ini dilakukan pada aspek motivasi kerja dan kerjasama. Target pelatihan ini adalah tenaga professional. Tenaga professional ini adalah Kepala sekolah, guru dan tenaga kependidikan. Berkaitan hal diatas, pelatihan ini diberikan kepada tenaga professional yang bekerja di Sekolah Dasar Islam Creative Kota Banjarbaru Kalimantan Selatan, Indonesia. Pelatihan ini diikuti 20 orang peserta yaitu tenaga pendidik dan staf. Proses pelatihan ini ada 2 proses, di dalam ruangan dan di luar ruangan. Di dalam ruangan dilakukan dengan pemberian materi tentang kepemimpinan dan motivasi. Sedangkan di luar ruangan dilakukan kegiatan pengaplikasian melalui simulasi mengenai kepemimpinan dan motivasi.